Experiencing authenticity to environmentally responsible behavior: Assessing the effects of perceived value, tourist emotion, and recollection on industrial heritage tourism - Zhang, Tao; Wei, Chen; Nie, Lingyue (Frontiers in Psychology, 2022)
As an important part of cultural heritage, industrial heritage has important cultural, historical and economic values. There are many researches on authentic experience in our country’s industrial heritage sites, but the studies on responsible behavior of authentic experience to environment are still lacking. Therefore, this study takes Nanjing Quarry Park as the research object and SOR theory as the theoretical basis, after combing the literature on five aspects of authentic experience, perceived value, emotion, tourists’ recollection and environmentally responsible behavior, the authors made questionnaires and conducted field research, the authentic data of tourists’ authentic experience in Nanjing Quarry Park were obtained by questionnaire and analyzed, and the research model of responsible environmental behavior of authentic experience in industrial heritage scenic spots was constructed. In conclusion, this study found that authentic experience and perceived value can induce positive and negative emotions in tourists, and then produce memories, and act on environmentally responsible behavior. Emotion plays a part of mediating role in authentic experience, perceived value, recollection and environmentally responsible behavior. Positive emotion and perceived value have significant positive effects on recollection and tourists’ responsible behavior, while negative emotion and perceived value have significant negative effects on recollection, there was no significant negative effect on responsible behavior of environment. Authentic experience is an important antecedent of emotion.